Blue Jeans Stage and Screen. Issue 1 (May 2019) - Mayer, David; Day-Mayer, Helen
Scholars of Victorian and Edwardian theatre necessarily piece together their accounts of ephemeral performance through manuscripts, reviews, and other responses preserved in print and visual culture. However, films made between 1895 and 1935 offer frequent, unexpected, and sometimes curiously skewed glimpses of the Victorian and Edwardian stage. This essay focuses on John H. Collins's 1917 silent film adaptation of Blue Jeans, Joseph Arthur's melodrama, popular from its New York debut in 1890. The melodrama is perhaps most famous for 'the great sawmill scene'. This iconic scene, an early example of an episode in which a helpless victim is tied to a board approaching a huge buzz saw, turns a mundane setting into a terrifying site for suspense, violence, and attempted murder. Whilst the film made alterations and abridgements, the overall effect was to preserve the play's distinctive features. Our essay shows how the stage version is preserved within Collins's film adaptation so that the cinematic artefact gives unique access to the Victorian theatrical work. Films not only preserve Victorian forms in modern media and extend the reach of Victorian culture, but also open a new resource and methodology for understanding Victorian and Edwardian theatre.